Christ/EL - Grützner, Andreas (Germany : Aug&Ohr Medien, 2016)
'Christ/EL' is a portrait told through Super 8 footage from 1975-77, and in its essence, is a documentary questioning personal belief. We are introduced to a man and his dilemma to stand up for his freedom, he struggles during adolescence and has strong urges to reach Christian enlightenment due to his family background. 'Christ/EL' is his family portrait.
Verzio Film Festival Submission
Keywords: Documentary films